If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6X + 15 + -5(X + 7) + 30 = 12 Reorder the terms: 6X + 15 + -5(7 + X) + 30 = 12 6X + 15 + (7 * -5 + X * -5) + 30 = 12 6X + 15 + (-35 + -5X) + 30 = 12 Reorder the terms: 15 + -35 + 30 + 6X + -5X = 12 Combine like terms: 15 + -35 = -20 -20 + 30 + 6X + -5X = 12 Combine like terms: -20 + 30 = 10 10 + 6X + -5X = 12 Combine like terms: 6X + -5X = 1X 10 + 1X = 12 Solving 10 + 1X = 12 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 1X = 12 + -10 Combine like terms: 10 + -10 = 0 0 + 1X = 12 + -10 1X = 12 + -10 Combine like terms: 12 + -10 = 2 1X = 2 Divide each side by '1'. X = 2 Simplifying X = 2
| 6x-5=6(x-1)+14 | | 10-43=2x+21 | | (9x+18)=54 | | 6y+5x=28 | | x^7=2.5 | | 3x-6=-2x+11 | | x^5-2x^4-x-3=0 | | 2c+4x=23 | | Y-3(-1)=4 | | Y-3(-2)=4 | | 3.0+3.0x=3.2 | | 4-x=[2-3x] | | 7-.625x=-2 | | .75x=180 | | 4(0)+2y=6 | | 100=10(logI-logI[0]) | | ax+by+1=0 | | 4(-1)+2y=6 | | 100=.50x-(15+.05x) | | 0.50x-(15+.05x)=100 | | (5x+1)(5x+1)=9 | | 2=6(5-4w) | | F-1(2)=2x-6 | | 8x+12y=144 | | 3(7a-1)= | | (3x-2)+(2x+4)+(x+10)=0 | | 8-2c=9 | | 52=-2w*3L | | 7-9g+8+2g= | | 10(-10x-5)= | | 10p+9-11-p=-4p+-8-6p-3 | | 7+9g-8+2g= |